2018
DOI: 10.1186/s12985-018-1093-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of equid alphaherpesvirus 1 strains isolated from aborted fetuses in Poland

Abstract: BackgroundEquid alphaherpesvirus 1 (EHV-1) is one of the main infectious causative agents of abortion in mares and can also be associated with stillbirth, neonatal foal death, rhinopneumonitis in young horses and a neurological disorder called equine herpesvirus myeloencephalopathy (EHM). The neuropathogenicity of the virus was shown to be significantly higher in EHV-1 strains that carry a single nucleotide point (SNP) mutation in the ORF30, which encodes a catalytic subunit of viral DNA polymerase (ORF30 D752… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…All the viruses described in the current report belonged to the ORF30 N 752 genotype, consistent with the predominance of the N 752 variants among EHV-1 abortion cases in Poland [ 25 , 57 ] and other countries [ 22 , 28 , 58 ]. While data from a recent investigation in Ireland [ 27 ] suggested that viruses with D 752 genotype were more likely not only to induce neurological disease, but also to be associated with multiple abortion cases as opposed to sporadic abortions, our results underscore the fact that infection with viruses of either N 752 or D 752 genotype should be considered equally important, and similar precaution/control measures should be implemented to minimise the economic losses due to disease outcomes associated with these infections.…”
Section: Discussionsupporting
confidence: 88%
“…All the viruses described in the current report belonged to the ORF30 N 752 genotype, consistent with the predominance of the N 752 variants among EHV-1 abortion cases in Poland [ 25 , 57 ] and other countries [ 22 , 28 , 58 ]. While data from a recent investigation in Ireland [ 27 ] suggested that viruses with D 752 genotype were more likely not only to induce neurological disease, but also to be associated with multiple abortion cases as opposed to sporadic abortions, our results underscore the fact that infection with viruses of either N 752 or D 752 genotype should be considered equally important, and similar precaution/control measures should be implemented to minimise the economic losses due to disease outcomes associated with these infections.…”
Section: Discussionsupporting
confidence: 88%
“…Thirty-four out of 269 isolated in Ireland between 1990 and 2017 showed N752D [12], and only two out of 56 EHV-1 isolated from aborted fetuses in India had the neuropathogenic marker [8]. The N752D genotype was not found in EHV-1 isolated in Brazil [23], in Turkey [24] and in the 27 strains isolated in Poland between 1993 and 2017 [11]. Even in other countries the prevalence of the neuropathogenic genotype was rather low, as in Japan (2.7%), the USA (10.8–19.4%), Argentina (7.4%), France (24%), and Germany (10.6%) [25,26,27,28,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing and analysis of the ORF68 gene are widely used for grouping EHV-1 [4,7,10,11]. An extensive study on ORF68 gene of EHV-1 isolated worldwide has been recently carried out [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations